The Impact Of E-Invoice Implementation on Taxpayer Compliance - Muhammad Adriansyah Panjaitan; Novien Rialdy (Institute of Advanced Knowledge and Science, 2024)
This study aims to determine the effect of the implementation of e-invoices on taxpayer compliance at the Medan City Tax Office. Because taxes are a source of state revenue to finance all expenses including development expenses, this greatly requires community participation in the form of awareness and concern for paying taxes. As is known, Indonesia adopts a self-assessment system. E-invoices are expected to be able to increase taxpayer compliance in paying their obligations. The method used in this study is a descriptive quantitative approach in the form of respondent answers in a questionnaire through a Likert scale. The population collection technique uses a simple random sampling technique with 2,320 taxpayers using E-invoices while the sample consists of 97 taxpayers, this is done using the Slovin formula. The data used comes from primary and secondary data. And the preparation of this thesis uses documentation and questionnaire data collection techniques. The hypothesis was tested using data normality test, simple linear regression analysis, partial t-test and R-Square using SPSS version 17. To determine the effect of e-invoice implementation on taxpayer compliance, simultaneously it has a significant effect on taxpayer compliance and statistical hypothesis testing was carried out with a calculated t value of 4.237> t table 1.661 with a significant value of 0.000 <0.05 which means that the better the implementation of the e-invoice application, the taxpayer compliance will also increase, thus Ha is accepted, it can be concluded that the implementation of e-invoice has a significant effect on taxpayer compliance.